Mistress of Mellyn (Doubleday, 1960)
Description Not Provided

Menfreya in the morning (Doubleday, 1966)
Description Not Provided

Kirkland revels (Doubleday, 1962)
Description Not Provided

The black opal (Doubleday, 1993)
Description Not Provided

The judas kiss (Doubleday, 1981)
Description Not Provided

On the night of the seventh moon (Doubleday, 1972)
Description Not Provided

Daughter of deceit (Doubleday, 1991)
Description Not Provided